Ordinary Sudan, 1504-2019 From Social History to Politics from Below Volume 1 | Volume 2 - Jalil, Mahassin Abdul; Seri-Hersch, Iris; Poussier, Anael; Revilla, Lucie; Vezzadini, Elena (Africa in Global History, 2023)
This book examines how ordinary people have induced the most important political shifts in the history of the Sudan, including the last 2019 Revolution but also how they have participated to the construction of consensus that regimes needed to survive. The two volumes of the book follow an organization according to discipline: the first is mostly on social history and the second on 'politics from below'.